A Comparative Analysis of Solar Thermal and Photovoltaic Systems with Heat-Pump Integration in a New-Build House Under Controlled Conditions - Christopher Tsang; Ljubomir Jankovic; William Swan; Richard Fitton; Grant Henshaw (Energies)
This study investigates the relative benefits of solar thermal (ST) and photovoltaic (PV) systems integrated with air-source heat pumps for domestic hot water production in newly built residential buildings. Using calibrated DesignBuilder simulations of “The Future Home” located in Energy House 2.0, an environmental chamber, the study analyzes energy performance and carbon emissions for eight scenarios: (1) baseline heat pump only, (2) heat pump with 4 m2 PV panels, (3) heat pump with 4 m2 ST panels, (4) heat pump with 2 m2 PV + 2 m2 ST panels, and (5–8) variants with increased hot water demand. While ST systems directly heat water through thermal energy transfer, PV systems contribute to water heating indirectly by providing electricity to power the heat pump. The results show that the ST system provides 964.6 kWh of thermal energy annually, increasing to 1528 kWh with enhanced hot water demand, while a similarly sized PV system generates 532.5 kWh of electricity. The research reveals that Standard Assessment Procedure methodology’s fixed hot water demand assumptions could significantly underpredict solar thermal benefits, potentially discouraging UK house builders from adopting this technology.